The Emerging Applications of Artificial MicroRNA-Mediated Gene Silencing in Plant Biotechnology - Luis Alberto Bravo-Vázquez; Ana Marta Castro-Pacheco; Rodrigo Pérez-Vargas; Joceline Fernanda Velázquez-Jiménez; Sujay Paul (Non-Coding RNA)
Improving crop yield potential is crucial to meet the increasing demands of a rapidly expanding global population in an ever-changing and challenging environment. Therefore, different technological approaches have been proposed over the last decades to accelerate plant breeding. Among them, artificial microRNAs (amiRNAs) represent an innovative tool with remarkable potential to assist plant improvement. MicroRNAs (miRNAs) are a group of endogenous, small (20–24 nucleotides), non-coding RNA molecules that play a crucial role in gene regulation. They are associated with most biological processes of a plant, including reproduction, development, cell differentiation, biotic and abiotic stress responses, metabolism, and plant architecture. In this context, amiRNAs are synthetic molecules engineered to mimic the structure and function of endogenous miRNAs, allowing for the targeted silencing of specific nucleic acids. The current review explores the diverse applications of amiRNAs in plant biology and agriculture, such as the management of infectious agents and pests, the engineering of plant metabolism, and the enhancement of plant resilience to abiotic stress. Moreover, we address future perspectives on plant amiRNA-based gene silencing strategies, highlighting the need for further research to fully comprehend the potential of this technology and to translate its scope toward the widespread adoption of amiRNA-based strategies for plant breeding.